THE ROLE OF LINGO-1 AND MYELIN BASIC PROTEIN MRNAS IN CENTRAL REMYELINATION IN ETHIDIUM BROMIDE-INDUCED DEMYELINATION IN RATS - HANAA ABOELKASEM ALAZRAG,; MERVAT EID ABDELGHAFFAR,; HUDA MAHMOUD KHALIFA,; RASHA MOHAMED ADEL NASSRA,; AMANY ALI KHALIL NAWAR, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study aimed to assess the possible role of quercetin, pioglitazone, metformin, and dapagliflozin in the enhancement of remyelination process after ethidium bromide (EB)-induced demyelination. Methods: The study was conducted on 60 male Wister rats (250–300 g), randomly divided into sham-operated group and five demyelination groups (each of 10 rats) which subjected to intrapontine stereotaxic injection of EB (10 μl of 0.1% EB) to induce demyelination. Then, randomly subdivided into: EB control group: Rats were treated with normal saline, quercetin-treated group (50 mg/kg/day), pioglitazone-treated group (10 mg/kg/day), metformin-treated group (500 mg/kg/day), and dapagliflozin-treated group (10 mg/kg/day). Behavioral tests (beam balance, foot fault, rotarod, and inverted screen) were conducted for all groups as well as biochemical analysis of LINGO-1 and myelin basic protein (MBP) mRNAs and histological examination of pontine tissues. Results: The EB control group showed deterioration of motor performance on behavioral tests. Degenerative changes were observed in pontine tissue on histological examination together with upregulation of LINGO-1 protein and downregulation of MBP level. While the treated groups after EB demyelination showed significant improvement in motor performance and decreased degenerated neurons in histological examination with upregulation of MBP level and downregulation of LINGO-1 protein level. Conclusion: Quercetin, metformin, dapagliflozin, and pioglitazone showed neuroprotective effect and enhancement of remyelination process.